An individual ZnO microwire homojunction LED with ultraviolet electroluminescence spectrally purified using Pt nanoparticles cladding. (May 2023) - Wang, Dailong; Liu, Maosheng; Shang, Shenao; Wan, Peng; Shi, Daning; Kan, Caixia; Li, Binghui; Jiang, Mingming
Graphical abstract: Highlights: Individual Sb-doped ZnO MWs with highly-crystallized quality were chemically synthesized. The p-type conductivity of individual ZnO:Sb MW is identified through a single wire field-effect transistor. The proposed p-ZnO:Sb MW/ n -ZnO homojunction LED can emit a broadband ultraviolet light. The ultraviolet electroluminescence of as-constructed p-ZnO:Sb/ n -ZnO homojunction LED was spectrally purified using PtNPs decoration. Abstract: Low-dimensional ultraviolet light sources are enormous significance due to their wide range of potential applications, ranging from bioscience and high-resolution biological imaging, environmental conservation to public hygiene. Nevertheless, developing energy-efficient and cost-efficient light sources still remains serious challenges. In this study, p-type ZnO microwires with Sb-incorporation (ZnO:Sb MWs) were synthesized individually. The p-type conductivity was proofed using an individual MW based back-gated field-effect transistor; while the ZnO:Sb MWs with quadrilateral cross-section exhibited stimulated emission resonant in well-defined Fabry-Perot mode on the benefit of single-crystalline quality and atomically smooth side facets. The newly synthesized ZnO:Sb MW was further used to fabricate homojunction light-emitting device by employing n -type ZnO film as electron-transporting layer. A strong ultraviolet emissions peaking at around 378.5 nm was achieved upon forward biased electrically, but illustrating much broader electroluminescence (EL) linewidth. Introducing Pt nanoparticles (PtNPs) with desired plasmons, the light-out intensity is significantly enhanced. Particularly, the broad EL profiles narrowed to about 16.6 nm at high injection regime, achieving electron-holes radiative recombination in the ZnO:Sb MWs active region. The results exhibit a prominent progress achieving high-quality ZnO nano/microstructures with genuine p-type conductivity, which has great hopes for its future applications and development in ZnO homojunction optoelectronic devices.